Motivations, delivery, perceived benefits, and barriers to delivery of the parkrun practice initiative in general practices across the UK: a national cross-sectional online survey of healthcare professionals and event organisers - Callum J. Leese; Ross Clarke; Robert H. Mann; Rosina Cross; Hussain Al-Zubaidi; Blair H. Smith; Emma J. Cockcroft (BMC Primary Care)
Abstract Background Physical activity offers significant health benefits, yet many people in the United Kingdom do not meet recommended guidelines. Primary care plays a crucial role in physical activity promotion, but barriers can hinder implementation. The parkrun practice initiative, launched in 2018, aims to address these barriers by linking general practices with local parkrun events. Aim This study aimed to evaluate the parkrun practice initiative from the perspective of staff at general practices and parkrun event organisers, exploring the motivations for joining, the variety of ways in which the initiative was delivered, perceived benefits on patients and staff, and barriers to implementation. Methods A cross-sectional online survey was distributed via email to 1,852 registered parkrun practices and 800 ‘linked’ parkrun event organisers. Descriptive statistics were used to present quantitative data. Content analysis was used to analyse qualitative data. Results Responses from 416 staff at parkrun practices (22% of registered practices) and 439 event organisers (55% of all events organisers) were included in the analysis. Attendance of staff at the local parkrun and sharing of information with patients were the main means of initiative implementation. Our findings highlight the perceived benefits of the initiative on staff and patient health and wellbeing, parkrun practice staff morale, and community engagement. A discrepancy is noted between what is being done by practices and what is being perceived by event organisers. Major barriers to implementation included: a lack of time; a lack of engagement of practice staff; the COVID-19 pandemic; and access to the nearest parkrun. Conclusion To address the barriers in implementing the parkrun practice initiative in primary care, our findings indicate that future initiatives should look to include: (1) clear and ongoing communication to ensure widespread engagement of patients, staff and event organisers; (2) ease of implementation (minimising time demands); and (3) adequate resource allocation to facilitate implementation (e.g., financial, educational, personnel). Further research is required to increase understanding of the impact on patient outcomes, staff morale, and the behavioural mechanisms influencing initiative implementation.